CTLA-4 (+49A/G) and NOD2/CARD15 (N852S) polymorphisms with inflammatory bowel disease in Turkish patients - Budak Diler, Songül; Yaraş, Serkan (Cellular and Molecular Biology, 2018)
Crohn’s disease (CD) and ulcerative colitis (UC) are the major types of inflammatory bowel disease (IBD) and exhibit similar clinical features and epidemiology. The main objective of this study was to analyze the correlation between the CTLA-4 gene +49A/G polymorphism and the NOD2/CARD15 gene N852S polymorphism in Turkish patients with IBD using polymerase chain reaction and restriction fragment length polymorphism (PCR-RFLP) analysis. In this study, we evaluated the frequency of the CTLA-4 (+49A/G) and NOD2/CARD15 (N852S) polymorphisms in 62 patients with CD, 76 patients with UC, and 152 healthy individuals. The CTLA-4 and NOD2/CARD15 variants, rs231775 and rs104895467, were genotyped by PCR followed by RFLP. The results for the patients and the control group were statistically analyzed. According to our results, the CTLA-4 gene +49A/G polymorphism AA genotype was prevalent in CD patients and controls (29% vs 40%); the AG (56% vs 51%) and GG (15% vs 9%) genotypes were also observed. The prevalence of the of AA, AG and GG genotypes for the +49A/G polymorphism was 56%, 32% and 12%, respectively, in the UC patients, and 40%, 51% and 9%, respectively, in the healthy controls. In all subjects, just one band of 151 bp, corresponding to wild-type N852S, was found, and no other N852S mutant bands (151+129+22 and 129+22 bp) were detected using PCR-RFLP fragment electrophoresis.The CTLA-4 gene +49 A/G polymorphism and the NOD2/CARD15 gene N852S polymorphism were not associated with CD or UC in a Turkish population.